Bengali and Dutch: A Phonological Contrastive Analysis of the front Monophthongs - Haque, Mohammed Shahedul; Sharfuddin, Nashrah (Research in Language, 2025)
This paper investigates the monophthongs of Bengali and Dutch, analyzing the similarities and differences in the phonetic characteristics between the two languages, particularly focusing on front monophthongs. The study determines the challenges faced by Bengali-speaking learners of Dutch (BLD) and Dutch-speaking learners of Bengali (DLB) as a foreign language. Using a quantitative-contrastive phonemic analysis (Haque, 2015; Haque & Jannat, 2022; Haque & Sharfuddin, 2023), the study mathematically demonstrates that BLD learners face greater difficulty in acquiring their target language, as Dutch has twice as many front monophthongs as Bengali. Additionally, no front vowels in both languages share identical phonetic qualities, and there are no mutual phonemes. These phonological differences indicate significant challenges for learners in acquiring their target languages.